A case report: Female primary urethral carcinoma presenting as vulval mass - Balagobi, B.; Abiharan, P.; Nalini, R.; Chrishanthi, R.; Theepan, J.; Heerthikan, K. (Elsevier, 2023)
Introduction: Primary urethral carcinoma is a rare disease with overall poorer outcomes in the past. It is relatively more uncommon in female sex. Clinical presentation: We present a case of a female with primary urethral carcinoma that presented atypically as a vulval mass without any features of storage, voiding lower urinary tract symptoms, or gross haematuria. Discussion: As primary urethral carcinoma is rare in occurrence, prospective studies are limited so as the rec- ommendations to guide treatment options. Treatment recommendations are still on development from different small-scale studies as well as from data in higher volume centers. Management options depends on location, extent, histology of the lesion as well as on sex of the patient and fitness of the patient. Conclusion: Early diagnosis and treatment with multidisciplinary consult and multimodality will improve the overall survival rate and quality of life of the patients.
Keywords: Urethral carcinoma; Cystourethroscopy; Vulval mass; Differential diagnosis